2013
DOI: 10.1007/s00011-013-0672-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of the immune system in idiopathic nephrotic syndrome: a review of clinical and experimental studies

Abstract: Idiopathic nephrotic syndrome (INS) is a multifactorial disease, characterized by proteinuria, hypoalbuminemia, edema and hyperlipidemia. Studies in humans and animal models have associated INS with changes in the immune response. The purpose of this article is to review clinical and experimental findings showing the involvement of the immune response in the pathogenesis of INS. The role of the immune system in INS has been shown by clinical and experimental studies. However, the pattern of immune response in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(19 citation statements)
references
References 83 publications
1
18
0
Order By: Relevance
“…It was reported that the severity of NS is associated with the decreased activity of Treg cells [9,11,12]. Similar finding showed that peripheral blood mononuclear cells (PBMC) of children with NS exhibited a reduction in Treg cells that is in parallel to an increase in Th17 cells [13].…”
Section: Introductionsupporting
confidence: 65%
See 3 more Smart Citations
“…It was reported that the severity of NS is associated with the decreased activity of Treg cells [9,11,12]. Similar finding showed that peripheral blood mononuclear cells (PBMC) of children with NS exhibited a reduction in Treg cells that is in parallel to an increase in Th17 cells [13].…”
Section: Introductionsupporting
confidence: 65%
“…Similar finding showed that peripheral blood mononuclear cells (PBMC) of children with NS exhibited a reduction in Treg cells that is in parallel to an increase in Th17 cells [13]. Treg cells have an anti-inflammatory role and maintain tolerance to self-components through direct contact with cells or by releasing anti-inflammatory cytokines such as IL-10 and TGF-β [9,14]. Nevertheless, Th17 cells play a key role in induction of autoimmune tissue injuries and inflammation by releasing IL-17 [15].…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…Conversely, regulatory T-cells (T Reg ) is an important tolerogenic T-cell possessing protective effect on podocyte destruction [6,7]. Vitamin D has been known as immunomodulator that able to induce T Reg differentiation as it has pleiotropic effects [8,9].…”
Section: Introductionmentioning
confidence: 99%